2022
DOI: 10.1155/2022/2663834
|View full text |Cite|
|
Sign up to set email alerts
|

A Deep Learning and Clustering Extraction Mechanism for Recognizing the Actions of Athletes in Sports

Abstract: In sports, the essence of a complete technical action is a complete information structure pattern and the athlete’s judgment of the action is actually the identification of the movement information structure pattern. Action recognition refers to the ability of the human brain to distinguish a perceived action from other actions and obtain predictive response information when it identifies and confirms it according to the constantly changing motion information on the field. Action recognition mainly includes tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Event detection technology refers to a set of tools and methods aimed at identifying and analyzing significant occurrences or patterns within a given data stream or system [1]. This technology often relies on advanced algorithms and machine learning techniques to sift through vast amounts of data in real-time, pinpointing events of interest and flagging them for further analysis or action [2]. One common application of event detection technology is in the realm of security and surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…Event detection technology refers to a set of tools and methods aimed at identifying and analyzing significant occurrences or patterns within a given data stream or system [1]. This technology often relies on advanced algorithms and machine learning techniques to sift through vast amounts of data in real-time, pinpointing events of interest and flagging them for further analysis or action [2]. One common application of event detection technology is in the realm of security and surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…Clustering approaches are unsupervised learning techniques that separate data into groups called clusters according to the similarities and dissimilarities among the data [ 1 , 2 ]. The DBSCAN [ 3 ], kmeans [ 4 ], BIRCH [ 5 ], Spectral Clustering [ 6 ], Agglomerative Clustering [ 7 ], HDBSCAN [ 8 ], Affinity Propagation [ 9 ], and OPTICS [ 10 ] are some examples of them, and they are used in many fields such as pattern recognition [ 11 13 ], machine learning [ 14 – 16 ], data mining [ 17 , 18 ], web mining [ 1 , 19 ], bioinformatics [ 20 , 21 ], and streaming data mining [ 22 , 23 ]. On the other hand, measuring the performance of any proposed clustering approach is also an important issue because each algorithm has its special point of view, and the results of each clustering technique vary.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%